Structural Characterization of Calcium Sulfate Bone Graft Substitute Cements - Favvas,Evangelos P. (2016)
The aim of this work was to study the structural characteristics of commercially available bone graft substitute (BGS) ceramic cements. In particular, the microstructure of two calcium sulfate cements was investigated. For this purpose, nitrogen and mercury porosimetry, x-ray diffraction (XRD) and scanning electron microscopy (SEM) measurements have been carried out. Mercury intrusion porosimetry results revealed that the structural characteristics of the two samples varied significantly. These structural differences can be justified when compared with their compression and bending strength properties. As a result, a proper understanding of microstructure of BGS materials is crucial in the search of what is optimal for bone regeneration.